Tempeh, a local plant-based ingredient, and its application in gluten-free noodles with potential as a VO₂Max booster : A review - Yudhistira, Razzan Aldrich; Waziiroh, Elok; Tridtitanakiat, Pavalee Chompoorat; Murtini, Erni Sofia (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2025)
The growing global demand for gluten-free products has positioned them as one of the most rapidly expanding trends in the food industry. Originally developed for individuals with celiac disease, gluten-free products have evolved into a wider market segment with significant development potential. In Indonesia, noodles represent an ideal medium for developing gluten-free food innovations due to their popularity and the availability of local raw materials. However, gluten-free noodles often face challenges related to poor texture and unbalanced nutritional composition, primarily due to the absence of gluten, which impairs dough elasticity and structural integrity. Beyond addressing these issues, gluten-free noodles can be further innovated as functional foods capable of enhancing VO₂Max. Emerging evidence suggests that the consumption of foods rich in the arginine amino acid, polyphenol and dietary nitrates can theoretically increase oxygen uptake, thereby enabling individuals to perform physical activities at elevated intensities and for extended durations without fatigue. Arginine and polyphenol is notably abundant in tempeh, a traditional Indonesian fermented soybean product, while nitrates are prevalent in leafy green vegetables such as spinach. By strategically selecting and combining raw materials with proven efficacy in improving gluten-free noodle quality, it is possible to develop products exhibiting favorable physicochemical and functional characteristics. In particular, the enrichment of arginine, polyphenol and nitrate contents holds promise due to their roles in nitric oxide synthesis and consequent enhancement of VO₂Max. The findings are expected to contribute to the advancement of nutritious and functional gluten free noodle products utilizing tempeh, a locally sourced Indonesian ingredients. This review not only advances gluten-free product innovation but also contributes to functional food development targeting improved physical performance.